Percutaneous In situ Left Subclavian Artery Fenestration Using Reentry Catheter during Endovascular Thoracic Aortic Aneurysm Repair - Tan, Tze-Woei; Coulter, Amy H.; Zhang, Wayne W. (International Journal of Angiology, 2016)
Left subclavian artery (LSA) revascularization is recommended during elective thoracic endovascular aortic aneurysm repair (TEVAR) when coverage is required for adequate proximal seal. Reported method for LSA revascularization includes open bypass, covered stent placement using chimney technique, and in situ laser fenestration. We reported a novel technique using percutaneous Outback reentry device for LSA revascularization in a 68-year-old male patient who underwent TEVAR for a 9-cm thoracic aortic aneurysm. This technique can be used as an alternative method for LSA in situ fenestration, and laser equipment is not required.
Keywords: endovascular repair; thoracoabdominal aortic aneurysm; subclavian; aneurysm; endograft placement; endovascular procedure; subclavian stenosis